Improving Mathematics Learning Outcomes on Composite Addition Through the Demonstration Method Using the Labyrinth Board Media for Grade II SDN 1 Mojowetan - Wahyu Ari Saputra; Anna Mariyani; Ahmad Teguh Purnawanto (Program Studi Pendididikan Guru Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2026)
This study aims to improve the learning outcomes of second-grade students of SDN 1 Mojowetan on the material of stacked addition through the application of the demonstration method with a labyrinth board media. The subjects of the study were 23 students of class II A. This study used the Classroom Action Research (CAR) method with the Kemmis and Mc. Taggart model, implemented in two cycles, each consisting of planning, implementation, observation, and reflection. Data collection techniques included observation, interviews, documentation, and tests, with data validity tested using source and method triangulation. Data analysis was carried out qualitatively and descriptive statistics. The pretest results showed that only 4 students with a percentage (17.39%) achieved the Minimum Completion Criteria (KKM). After the application of the demonstration method and maze board, learning outcomes increased significantly, as many as 12 students with a percentage (52.17%) achieved completion in cycle 1, and increased to 20 students with a percentage (86.96%) in cycle 2. In addition to cognitive outcomes, the results of teacher skills in applying the demonstration method in cycle I got an average score of 17 with the category (Good), while in cycle 2 there was an increase with an average score of 19 with the category (Very Good) from a total score of 20. In conclusion, the application of the demonstration method with maze board media effectively improves the quality of learning and student outcomes.